If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(0+1)=4(x+8)
We simplify the equation to the form, which is simple to understand
4(0+1)=4(x+8)
Reorder the terms in parentheses
+(+4)=4*(x+8)
Remove unnecessary parentheses
+4=+4+*(+x+8+)
Reorder the terms in parentheses
+4=+(+4x+32)
Remove unnecessary parentheses
+4=+4x+32
We move all terms containing x to the left and all other terms to the right.
-4x=+32-0-4
We simplify left and right side of the equation.
-4x=+28
We divide both sides of the equation by -04 to get x.
x=-7
| 22+2z=52 | | 9d+1=8d-18 | | 3(g+8)-2=7 | | 6x^6-96x^2=0 | | 4x+8=15x-3x | | -4=5+3n | | 0=2(sin)x*2(cos)x | | 6-x=42 | | (2u+5v)(2u-5v)= | | -28x+24-3x-12=30 | | 104x=3x+6 | | 17/2+1/2= | | 6a+3=3a+15 | | 0=2sinx*2cosx | | 2y+7x=-5 | | 2=4r+n | | 3+17+5x=7x+10 | | 99=2d-419 | | h(1)=5 | | -x^2+9x=16 | | 6(5y-8)-(4y+7)= | | 4(-7x+6)-3(x-2)=30 | | 8t^2+64=0 | | 3-2(4n-6)=5(n+4) | | -2(n+1)=0 | | X^4+20=21 | | 69+2u=-23 | | 8x-(3x-17)=52 | | 5y+2x=19 | | -2x+2=-7+17 | | 15-(-30s)=465 | | 3(x-1)4+7=19 |